2013
DOI: 10.1155/2013/964737
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Urban Runoff Pollution between Dissolved and Particulate Phases

Abstract: To develop urban stormwater management effectively, characterization of urban runoff pollution between dissolved and particulate phases was studied by 12 rainfall events monitored for five typical urban catchments. The average event mean concentration (AEMC) of runoff pollutants in different phases was evaluated. The AEMC values of runoff pollutants in different phases from urban roads were higher than the ones from urban roofs. The proportions of total dissolved solids, total dissolved nitrogen, and total dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…The data showed that these events had low rain and runoff volume, and occurred after storms with low rain and runoff volume (<40% runoff) ( Fig 3A). Wei et al [56] suggested that particulate matter might be intercepted by coarse surfaces during low stormwater runoff from previous events, thus debris stuck in the storm drains was not flushed, resulting in high PON concentrations in the subsequent samples.…”
Section: Concentrations and Loads Of Nitrogen Forms In Stormwater Runoffmentioning
confidence: 99%
“…The data showed that these events had low rain and runoff volume, and occurred after storms with low rain and runoff volume (<40% runoff) ( Fig 3A). Wei et al [56] suggested that particulate matter might be intercepted by coarse surfaces during low stormwater runoff from previous events, thus debris stuck in the storm drains was not flushed, resulting in high PON concentrations in the subsequent samples.…”
Section: Concentrations and Loads Of Nitrogen Forms In Stormwater Runoffmentioning
confidence: 99%
“…Due to abnormal data, spearman correlation test was used. According to the presented results in Table (5), TOC concentration has an insignificant relationship with the distance from the road.…”
Section: Effect Of Distance From the Road On Tocmentioning
confidence: 91%
“…Many rural and urban households in Africa rely on rainwater harvested from roof catchments to provide water for use [2][3] . Rainwater harvesting (RWH) is the collection of rainwater from a surface known as catchment (roofs and ground surfaces); and its storage in physical structures or within the soil profile [4][5][6] . Although rainwater harvesting has been identified as among the important interventions necessary towards meeting the MDGs in Africa [5] , roof runoff is known as a potential source of nonpoint pollution [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Although rainwater harvesting has been identified as among the important interventions necessary towards meeting the MDGs in Africa [5] , roof runoff is known as a potential source of nonpoint pollution [7] . Urban residential roofs are made up of different materials containing compounds that can leach into rainwater together with atmospherically deposited materials that easily dissolve into the runoff [6,8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation